Empowering Small and Medium Enterprises: The Impact of People's Credit Banks in North Sumatera - Simanjuntak, Markus Doddy; Sitorus, Sunday Ade (Pusat Riset dan Inovasi Nasional, 2022)
Micro, Small and Medium Enterprises are one of the components of business that have a large enough role in creating jobs in Indonesia, and advancing the economy. MSMEs have a strategic role in driving national economic development. People's credit banking efforts in developing the country's economy are to provide financing to the real sector through micro, small and medium enterprises. Along with the government's attention to the development of MSMEs in Indonesia, Rural Banks have also participated in empowering MSMEs, providing support with various strategies, such as by establishing micro-financing service centers such as MSME outlets or MSME centers,